Effects of an environmental endocrine disruptor, para‐nonylphenol on the cell growth of Euglena gracilis: association with the cellular oxidative stress. Issue 1 (15th December 2021) - Okai, Yasuji; Okuwa‐Hayashi, Hirotaka; Higashi‐Okai, Kiyoka; Yamane, Takuya; Tanaka, Yoshiharu; Inui, Hiroshi; Sakamoto, Tatsuji; Nakano, Yoshihisa
Summary: Effects of an environmental endocrine disruptor, para ‐nonylphenol (NP) on the cell growth of a photosynthetic eukaryotic microorganism, Euglena gracilis were analysed under different cell culture conditions. Although NP did not show significant inhibitory effects on the cell growth of E. gracilis (Z and SM strains) under light culture condition, NP exhibited significant suppressive effects under dark culture condition. Exogenous supplementation with lipophilic antioxidants (α‐tocopherol, β‐carotene or 6‐ O ‐palmitoyl‐ascorbic acid) to E. gracilis caused strong preventive effects against NP‐induced cell growth inhibition under dark culture condition, but hydrophilic antioxidants [ascorbic acid, glutathione and epigallocatechin gallate (EGCG)] did not show significant preventive effects. NP caused significant generation of reactive oxygen species (ROS) in E. gracilis under dark culture condition, but E. gracilis under light culture condition did not show significant increase in ROS generation. Supplementation with lipophilic antioxidants to E. gracilis caused significant suppressive effects against NP‐induced cellular ROS generation under dark culture condition, but hydrophilic antioxidants did not show significant suppressive effects. Furthermore, the productivities of typical cellular antioxidants (α‐tocopherol, β‐carotene and ascorbic acid) in E. gracilis under light culture conditions were much higher than those under dark culture conditions.